Phosphate buffer-catalyzed kinetics of mutarotation of glucosamine investigated by NMR spectroscopy. (July 2022) - Rivlin, Michal; Navon, Gil
Abstract: Glucosamine (2-amino-2-deoxy-d -glucose, GlcN) is a naturally occurring amino monosaccharide that is essential for a variety of biological functions, it is mainly involved in the formation of polysaccharide structures. It was recently reported to enable the imaging of cancerous tumors as an exogenous contrast agent using the MRI technique of chemical exchange saturation transfer (CEST). In preparation for the clinical use of GlcN, its anomeric equilibrium and mutarotation rate constants were directly investigated in this study utilizing high resolution 1 H and 13 C NMR spectroscopy. The effects of GlcN concentration, temperature, pH and buffer on the mutarotation rate constant and mutarotation equilibrium were measured. The mutarotation rate constant increased markedly with increasing GlcN concentrations. The rate constant of mutarotation of GlcN at room temperature was 2.2 × 10 −4 - 5.0 × 10 −4  s −1  at concentrations of 0.02–0.5 M, corresponding to a time of 3.8–1.7 h to reach 95% equilibrium. The anomeric ratio was strongly pH-dependent. The influence of phosphate buffer on the apparent rate constant of GlcN mutarotation was investigated. For phosphate buffer saline values between 0 and 50 mM, there was a six-fold increase in rate at pH 7.0. The mutarotation rate constant rose rapidly with pH at a phosphate concentration of 50 mM: from 0.4 × 10 −3  s −1  at pH 5.0 to 7.8 × 10 −3  s −1  at pH 9.4, suggesting that the catalysis is due to the HPO4 2− and PO4 3− ions. These findings might help researchers design the experimental setting for employing GlcN for cancer detection using GlcN-CEST MRI. Graphical abstract: Image 1 Highlights: The kinetics of GlcN mutarotation was directly determined by 1 H and 13 C NMR. Rate constants of GlcN mutarotation increase with increasing amino concentration. The anomeric ratio of GlcN is pH dependent due to protonation of the amine. Phosphate-catalysis impacts GlcN anomerization rate due to HPO4 2− and PO4 3− . Phosphate-GlcN and GlcN-GlcN interactions have opposite effects on anomeric ratio.